PROBLEMS OF FORMING PROFESSIONAL SKILLS IN STUDENTS OF MAQOM SINGING (World Bulletin of Education and Learning, 2025)
Naturally, various forms and melodies can emerge in the process of creating and interpreting classical examples of musical heritage. As a result, various performance styles and schools related to the artistic interpretation of works have formed within the traditional performance movement. These styles have undergone changes and transformations in musical practice over many periods, developing on the basis of a certain creative system and stylistic rules, and occupying their rightful place. In this article, the issues of forming professional skills in student maqom singers are scientifically analyzed.
Keywords: Maqom, singer, professional skills, musical art, student, performance, melody, style, curriculum, didactic criterion.